2018
DOI: 10.1111/hel.12543
|View full text |Cite
|
Sign up to set email alerts
|

Successful Helicobacter pylori eradication therapy improves symptoms of chronic constipation

Abstract: Backgrounds and Aims Constipation is one of the most common gastrointestinal functional disorders. Recently, the gut microbiota has been implicated in the development of constipation. Helicobacter pylori infection is considered to be a possible factor influencing the gut microbiota profile. Here, we investigated the effect of H. pylori eradication therapy on symptoms of chronic constipation. Methods We recruited 166 H pylori‐positive patients who underwent eradication therapy after endoscopy. We evaluated the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 46 publications
1
12
0
Order By: Relevance
“…Murata et al . revealed that anti‐ H. pylori therapy improved symptoms of chronic constipation . On the other hand, Imase et al .…”
Section: Discussionmentioning
confidence: 99%
“…Murata et al . revealed that anti‐ H. pylori therapy improved symptoms of chronic constipation . On the other hand, Imase et al .…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we also found that the richness and diversity of gastric species were lower in H. pylori -positive patients than in H. pylori -negative patients according to alpha diversity indexes. In recent years, it has been reported that there is a significant difference in the gastric mucosal microbiota between H. pylori -positive and H. pylori -negative subjects ( Murata et al., 2018 ; Park et al., 2019 ; Miftahussurur et al., 2020 ), and that H. pylori infection has also been found to have a significant impact on the structure of the gastric microbiota in animal models ( He et al., 2016 ; Kienesberger et al., 2016 ; Miao et al., 2020 ). Among individuals infected with H. pylori , the dominant bacterial categories in the stomach are mainly Proteobacteria , Firmicutes , and Actinobacteria .…”
Section: Discussionmentioning
confidence: 99%
“…Until now, only a few studies have shown less frequent diarrhea after therapy, but it has been combined with probiotic use [ 26 , 27 ]. Additionally, eradication therapy might improve constipation symptoms, as shown by Murata et al [ 28 ]. In the case of constipation and diarrhea, we can assume that less antibiotics may have a less negative influence on gut microbiota, which can lead to less disturbance in bowel movement.…”
Section: Discussionmentioning
confidence: 99%